Pengaruh Penggunaan Media Tiga Dimensi Terhadap Kemampuan Berpikir Analsisis Siswa Pembelajaran Tematik - Sari, Efinda; Sumarno, Sumarno; Setya Putri, Anggun Dwi (Jurnal Ilmiah Sekolah Dasar, 2019)
The background of this research is thematic learning in class V still using learning media that contains images in the book package. The purpose of the study was to understand the use of three-dimensional media on students' analytical skills. This type of research is quantitative research in the form of Pre Experimental Design with the type of Pretest-Posttest One Group. The population of this study was fifth grade students who gathered 27 students. Data collection uses test, observation, and documentation methods. The results of the assessment of students' thinking analysis before and after being given permission to use three-dimensional media need to be improved. Based on the results of the t-test know tcount 21.415> t table 1.706. The media conclusions are three positive and significant dimensions of students' analytical thinking abilities.